The first experience of lengthening enteroplasty for short bowel syndrome in a one-month-old baby in Ukraine - O.K. Sliepov; M.Y. Migur; O.P. Ponomarenko; O.P. Gladyshko; O.V. Markevich; G.О. Grebinichenko (Хірургія дитячого віку, 2020)
Closed gastroschisis is one of the rarest forms of gastroschisis, in which the prolapsed organs are pinched in a stenotic defect of the anterior abdominal wall. This leads to the development of local or total compression infarction of the eventrated midgut and the development of short bowel syndrome. Surgical treatment of this pathology is complex and multi-stage, and presents great difficulties for pediatric surgeons around the world.